PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE - Diah Ayu Agustin L, 11.05.52.0052; Indarti, MG Kentris (Students Journal of Accounting and Banking, 2016)
This study aims to examine the factors that affect the companyâs effective tax rate. There are several factors used include profitability, liquidity, leverage,and corporate governance. This research was conducted based on survey on The Indonesia Institute Corporate Governance (IICG) by using the companyâs analysis in the ranking on the Corporate Governance Perception Index (CGPI). The sampling methode for this research is using purpossive sampling with a period of study from 2011 until 2013. The influence of between variables are described using multiple analytical methods of regression. The researcch result showed that Profitability have the positive effect significantly to Effective Tax Rate, Liquidity have a positive significantly effect to the Effective Tax Rate. The researchâs result showed that Leverage the significant negative effect against the Effective Tax Rate, and Corporate Governanceâs effect the negative significant of Effective Tax Rate.Keywords: Profitability, Liquidity, Leverage, Corporate Governance, Effective Tax Rate